2010
DOI: 10.1007/s00467-009-1426-0
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular basement membrane lipidosis in Alagille syndrome

Abstract: Alagille syndrome is characterized by a paucity of interlobular bile ducts with chronic cholestasis, cardiac, skeletal, and eye abnormalities and is associated predominantly with JAG1 mutations. Various renal abnormalities have been sporadically described. The classic renal histopathology described in Alagille syndrome is mesangiolipidosis, with lipid deposits predominately confined to the mesangium and minimal deposition within the glomerular basement membrane (GBM). We report a 5-year-old girl with Alagille … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…Renal abnormalities, such as tubulointerstitial nephropathy, membranous nephropathy, single kidney and renovascular hypertension, may be prominent. [373][374][375] The most frequent finding is mesangiolipidosis. 376 Nephrolithiasis may occur, and various types of renal cystic disease have been reported.…”
Section: Paucity Of the Intrahepatic Bile Ductsmentioning
confidence: 99%
“…Renal abnormalities, such as tubulointerstitial nephropathy, membranous nephropathy, single kidney and renovascular hypertension, may be prominent. [373][374][375] The most frequent finding is mesangiolipidosis. 376 Nephrolithiasis may occur, and various types of renal cystic disease have been reported.…”
Section: Paucity Of the Intrahepatic Bile Ductsmentioning
confidence: 99%
“…In 1982, Moorhead and colleagues suggested that lipid accumulation induces kidney injury and can cause progressive renal disease. Recently, studies demonstrated that lipid abnormalities contribute to disease progression and GS …”
mentioning
confidence: 99%
“…4 M u y r a r a m e n t e , puede encontrarse glomeruloesclerosis focal y segmentaria, aunque solo ha sido descrita en 2 pacientes adultos. 2,8 A pesar de que, en ninguno de nuestros pacientes, se realizó biopsia renal, podría especularse que este grupo presentaba dichas lesiones histológicas como responsables de la disfunción renal. Esto destaca la importancia de la búsqueda de afectación renal en todos los pacientes, incluyendo aquellos sin patología estructural.…”
Section: Discussionunclassified
“…2,4,7 También han sido descritos cambios glomerulares, como la mesangiolipidosis y la glomeruloesclerosis focal y segmentaria. 2,8 La hipertensión arterial secundaria a estenosis de la arteria renal y otros compromisos vasculares, como el síndrome de aorta media, anomalías vasculares intraabdominales y del sistema nervioso central, también han sido descritos. 3 Los accidentes cerebrovasculares han sido reportados hasta en el 15%.…”
Section: Introductionunclassified